Pengaruh Kurikulum Merdeka Belajar Terhadap Kreativitas Belajar PAK Siswa Kelas VII SMP Negeri 4 Laguboti Kabupaten Toba Tahun Pembelajaran 2022/2023 - Natasya Silaban; Tianggur Napitupulu; Rida Gultom; Malani Simanungkalit; Limmarten Simatupang (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The aim of this research is to determine the positive and significant influence of the Merdeka Belajar Curriculum on the creativity of PAK learning of students in class VII of SMP Negeri 4 Laguboti, Toba Regency for the 2022/2023 academic year. The research method used in this research is a quantitative method with a descriptive statistical approach. The population is all class VII of SMP Negeri 4 Laguboti, Toba Regency, 2022/2023 academic year, totaling 190 people and a sample of 57 people was determined using random sampling technique. Data was collected using a positive closed questionnaire with 32 items. The results of data analysis show that there is a positive and significant influence of the Merdeka Belajar Curriculum on PAK learning creativity of students in class VII of SMP Negeri 4 Laguboti, Toba Regency for the 2022/2023 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.422> rtable(α = 0.05, IK=95%, n=57) = 0.254, thus it is known that there is a positive relationship between variable α=0.05,dk=n-2=55)=2,000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r²)=17.8%. Thus Ha is accepted and H0 is rejected.